Performance Enhancement of Optical CDMA by Differential-Phase Method for Radio-over-Fiber Transmissions. (18th November 2013) - Cheng, Hsu-Chih; Yen, Chih-Ta; Ding, Ing-Jr
Abstract : The study proposes the differential-phase optical code-division multiple-access (OCDMA) network for radio-over-fiber (RoF) transmissions, and the characteristics are numerically analyzed. The network coder/decoders (codecs) are structured on the basis of arrayed-waveguide-grating (AWG) routers with complementary Walsh-Hadamard (CWH) signature codes. In the proposed system, the network requires only two AWG routers to accomplish spectral encoding of radio base station (RBS) and decoding of control station for the complementary keying, thus resulting in a simpler and low cost system. Performance analyses are evaluated with the dominant noise of phase-induced intensity noise (PIIN) in spectral code OCDMA network. By the proposed AWG-based OCDMA with the differential-phase scheme, it is possible to establish interference-free and low crosstalk beat noise RoF systems.